ISASO2: recent trends and regional patterns of ocean dissolved oxygen change - N. Kolodziejczyk; E. Portela; V. Thierry; A. Prigent (Earth System Science Data)
Recent estimates of the global inventory of dissolved oxygen (DO) have suggested a decrease of 2 % since the 1960s. However, due to the sparse historical oxygen data coverage, the DO inventory exhibits large regional uncertainties over the interannual timescale. Using the In Situ Analysis System for O2 (ISASO2), a new Argo DO-based optimally interpolated climatology at https://doi.org/10.17882/52367 (Kolodziejczyk et al., 2023), we have estimated an updated regional oxygen inventory. Over the long term (∼ 1980–2013), comparing the ISASO2 Argo fields with the first-guess World Ocean Atlas (WOA18) built from the DO bottle sample fields extracted from the World Ocean Database 2018 (WOD18), the broad tendency to global ocean deoxygenation remains robust in the upper 2000 m, with −451 ± 243 Tmol per decade. The oxygen decline is more pronounced in the key ventilation areas of the Southern Ocean and North Atlantic, except in the Nordic Seas, where oxygen has increased. Over the shorter timescale of the Argo period (2005–2019), the deoxygenation tendency seems globally amplified (−1211 ± 218 Tmol per decade). However, DO changes exhibit stronger amplitude and contrasting regional patterns. The recent changes in Apparent Oxygen Utilization mainly explain the interannual variability in the ventilation regions. However, Argo DO coverage is still incomplete as global and calibration method development is still in progress. Continuing the monitoring of the seasonal-to-interannual and regional-to-global DO variability from ISASO2 will improve our ability to reduce uncertainties in global and regional DO inventories.